Almost Automorphic Functions of Order n and Applications to Dynamic Equations on Time Scales - Gisèle Mophou; Gaston Mandata N’Guérékata; Aril Milce (Discrete Dynamics in Nature and Society)
We revisit the notion on almost automorphic functions on time scales given by Lizama and Mesquita (2013). Then we present the notion of almost automorphic functions of order n. Finally, we apply this notion to study the existence and uniqueness and the global stability of almost automorphic solution of first order to a dynamical equation with finite time varying delay.